Persepsi Kepuasan Konsumen terhadap Produk Makanan Ringan Berbahan Baku Hasil Olahan Pertanian di Indomaret Unit Ir. Sukowati Pangkep - Virganita Brigadya; Abd. Asis Pata; Andi Nur Imran (Universitas Muslim Maros, 2023)
This study aims to determine the perception of consumer satisfaction with the purchase of snack products made from processed agricultural products. This research was conducted at Indomaret Ir. Sukowati Pangkep which is located on Jl. Ir. Sukowati, Padoang Doangan Village, Pangkajene District, Pangkep Regency. This type of research uses quantitative descriptive methods. The population in this study are consumers who shop for snack products made from processed agricultural products at Indomaret Ir. Sukowati Pangkep. The sample of respondents was taken using the Accidental Sampling method with a total of 30 respondents. The data used is obtained from the results of interviews and filling out questionnaires by consumers who have shopped for snack products made from processed agricultural products at Indomaret Ir. Sukowati Pangkep. The results obtained show that the level of consumer satisfaction with snack products made from processed agricultural products can be categorized as very satisfied. With 3 snack products with processed chips, namely Chitato from potato raw materials, Qtela from cassava raw materials, and Happy tos from corn raw materials. On variable indicators of product quality with average results in the very satisfied category, variable indicators of product prices with average results in the very satisfied category, and variable indicators of Indomaret Unit Ir. Sukowati Pangkep location with average results in the very satisfied category.